Examining the Eye Movement Behaviors Associated With Skilled Decision-Making by Elite Australian Rules Football Players - Kassem, Lael; MacMahon, Clare; Quinn, John; Dogramaci, Sera; Pang, Bonnie; Steel, Kylie A. (Frontiers in Sports and Active Living, 2022)
Exploration of eye-movement behaviors of humans can provide insight into the processes used to inform and make decisions, with a large body of research revealing general trends, especially in the sporting context. Despite this some questions remain within the sport context particularly for elite groups engaged in diverse sports, and the potential for this information to provide for training, development, and performance. Therefore, the purpose of this study was to examine the critical fixation points and durations associated with superior decision-making within an elite group of Australian Rules football players. To achieve this eye-movement behavior (fixations) and associated decision-making skills of (N = 27; Mage = 25.0 ± 3.7 yrs) elite Australian Rules (AR) football players were measured while they watched game-based video clips. The most skilled players made significantly faster decisions compared to less skilled players (p < 0.001), who also had significantly shorter total fixation duration (p < 0.0001). Further, analysis showed that the most skilled players spent more time fixating on potential options within an area of interest (p = 0.003). Thus, within a group of highly skilled group of athletes, distinctions can be made on perceptual-cognitive skills, for outcome decisions and decision processes. That is, skilled decision-makers appear to have more efficient visual search strategies, which may help them process visual information more effectively. Further, examination of these behaviors may aid sport science and coaching staff identify the process that can be refined to increase player ability between and within various teams.